2013
DOI: 10.4172/2329-6917.1000115
|View full text |Cite
|
Sign up to set email alerts
|

Oral Hygiene Status and Selected Saliva Biomarkers in Children with Acute Lymphoblastic Leukaemia During Anticancer Therapy

Abstract: Altered secretion of saliva and its changed composition in patients undergoing chemotherapy often results in oral mucosa pathologies. The aim of this study was to assess the impact of oral hygiene and the concentration of calcium, phosphate and magnesium ions in the saliva on developing oral mucositis in children with acute lymphoblastic leukaemia (ALL) during anticancer therapy. The study included 78 children, aged from 2 to 18 yrs suffering from ALL on anticancer therapy. The results of biochemical scores fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This could be associated to the oral hygiene practice other than the effect of the chemotherapy treatment .In accordance to that. Pels and Mielnik-Błaszcza [27] reported that oral hygiene status was particularly better in children with ALL compared to children from the control group. In contrast, Dontasky et al [28] found that the oral health status of hospitalized children diagnosed with leukaemia or other cancers is generally poor.…”
Section: Discussionmentioning
confidence: 98%
“…This could be associated to the oral hygiene practice other than the effect of the chemotherapy treatment .In accordance to that. Pels and Mielnik-Błaszcza [27] reported that oral hygiene status was particularly better in children with ALL compared to children from the control group. In contrast, Dontasky et al [28] found that the oral health status of hospitalized children diagnosed with leukaemia or other cancers is generally poor.…”
Section: Discussionmentioning
confidence: 98%
“…Chemotherapy along with administration of certain drugs like methotrexate and prednisone may impact the presence of oral lesions especially patients with ALL oral mucosal anomalies like shallow papillae, coated tongue, fetor oris, generalized ulcers, tender oral mucosa, and oral mucosal infections like candidiasis, herpes simplex, varicella/zoster, and cytomegalovirus are most common in patients with ALL [16,[27][28][29][30][31][32].…”
Section: Oral Mucositismentioning
confidence: 99%
“…While much attention is being paid to detect hormones or infectious diseases via rapid salivary testing, there has been less effort given to quantifying the levels of important, physiological indicators, such as the concentration of sodium ions. Quantitation of sodium ion levels in saliva can potentially be used to monitor patient wellness, track endogenous cycles, as well as to conduct screening for patients with chronic underlying diseases or those undergoing dialysis [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%